Engaging Students in Class Activities through GC Application - yustinia kusumastuti (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2018)
This paper discusses about the emergence of technology within class activities, in which students would definitely engaged. As turning in smartphones become a daily bread, teachers need to manage certain activities which is engaging, challenging and pushing students’ contribution, regardless to the flow of materials. GC application assists teachers to efficiently manage the class materials, link to any sites needed to enhance the materials, and display the assignments. Not only to enhance the materials, but also it helps teachers to maintain those students get along with the learning process and covers the necessary language skills.The research upon 2 classes revealed that teachers easily share the assignment and countlessly interact with the students. Assignment should be given in class time, so that comments and scores could be shared at once. Extended assignment would need longer time for students to complete, or even missed, so that works can’t be accomplished. The interactions between teachers and students are continuously grow, which means that the written skills is maintained. Also through the video projects uploaded, teachers would be able to check the pronunciation and other spoken skills. After all, the use of GC is reliable and challenging for both students and teachers.